2005
DOI: 10.1080/14756360500213231
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of reduced xanthatin derivatives andin vitroevaluation of their antifungal activity

Abstract: The synthesis of new xanthanolide derivatives is reported starting from xanthatin, a sesquiterpenic lactone isolated from Xanthium macrocarpum (Asteraceae). In vitro evaluation of their antifungal activity has been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…(Asteraceae), a native herb commonly used in China [ 4 , 5 ]. Previous studies demonstrated that xanthatin exhibits a wide variety of bioactivities, including anticancer [ 6 , 7 ], antiangiogenesis [ 8 10 ], antiviral [ 10 ], antiinflammatory [ 11 ], antifungal [ 12 , 13 ], antibacterial [ 14 ], antitrypanosome [ 11 ], and antileishmanial [ 13 ] activities. In addition, xanthatin was reported to suppress proliferation and induce apoptosis in a wide variety of cancer cell culture systems, including non-small cell lung cancer cells (A549 and H522 cells), MKN-45 human gastric carcinoma cells, MDA-MB-231 human breast cancer cells, B16-F10 murine melanoma cells, and L1210 mouse leukemia cells [ 9 , 10 , 15 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…(Asteraceae), a native herb commonly used in China [ 4 , 5 ]. Previous studies demonstrated that xanthatin exhibits a wide variety of bioactivities, including anticancer [ 6 , 7 ], antiangiogenesis [ 8 10 ], antiviral [ 10 ], antiinflammatory [ 11 ], antifungal [ 12 , 13 ], antibacterial [ 14 ], antitrypanosome [ 11 ], and antileishmanial [ 13 ] activities. In addition, xanthatin was reported to suppress proliferation and induce apoptosis in a wide variety of cancer cell culture systems, including non-small cell lung cancer cells (A549 and H522 cells), MKN-45 human gastric carcinoma cells, MDA-MB-231 human breast cancer cells, B16-F10 murine melanoma cells, and L1210 mouse leukemia cells [ 9 , 10 , 15 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown to have in vitro anticancer activities in human colon (WiDr cells) and breast (MDA‐MB‐231) cancer cells (Ramírez‐Erosa et al , ). In other studies, xanthatin showed bactericidal and fungicidal activities and its biological effects were correlated with the α‐methylene‐γ‐lactone part of its chemical structure (Ginesta‐Perls et al , ; Pinel et al , ). 8‐Epi‐xanthatin and 8‐epi‐xanthatin epoxide, which are the epimers of xanthatin, disturbed insect development (Kawazu et al , ), and showed antimalarial (Joshi et al , ), anti‐farnesyltransferase and cytotoxic properties (Kim et al , ).…”
Section: Discussionmentioning
confidence: 92%
“…The sesquiterpene lactone xanthatin is the major bioactive compound isolated from the leaves of Xanthium sibiricum. Xanthatin has beneficial biological activities such as antitumor, antifungal, and antiplasmodial effects [119][120][121]. Xanthatin was also shown to have antiangiogenic properties through the inhibition of the VEGFR2 signaling pathways [122].…”
Section: Non-flavonoid Phytochemicalsmentioning
confidence: 99%